Efficiency of Working Capital Use at PT Industri Jamu Dan Farmasi Sido Muncul, Tbk in 2019-2021 - Tyana, Bella Eka; Kantun, Sri; Tiara, Tiara (RIGGS: Journal of Artificial Intelligence and Digital Business, 2023)
This study aims to determine the efficiency of working capital use at PT Industri Jamu dan Farmasi Sido Muncul, Tbk in 2019-2021. This research uses a descriptive method with a quantitative approach. Data collection by using secondary data document methods. The data analysis method used is by calculating the ratio of working capital turnover, receivables turnover and inventory turnover. The results showed that the efficiency of using working capital of PT Industri Jamu dan Farmasi Sido Muncul during 2019-2021 in terms of the ratio of working capital turnover, receivables and inventory was included in the less efficient criteria. The working capital turnover ratio shows that the turnover frequency is less than the efficiency standard of industrial enterprises, which is 6 times the turnover. The receivables turnover ratio shows an average frequency below the efficiency standard of 15 times and the average life of receivables can be collected much longer than the standard life of receivables which is 25 days, while inventory turnover shows a turnover frequency result of less than the standard efficiency of 20 times with the average life of inventory can be sold much longer than the standard inventory life of 19 days.